Association between endothelial NO synthase polymorphisms and arterial properties in the general population - Seidlerová, Jitka; Filipovský, Jan; Mayer, Otto; Kučerová, Alena; Pešta, Martin (Nitric oxide, 2015)
OBJECTIVE: Nitric oxide plays an important role in vascular biology. Several single nucleotide polymorphisms (SNP) in the endothelial nitric oxide gene (NOS3) have been previously associated with arterial hypertension. We investigated whether these SNPs might be associated with arterial phenotypes in the Czech general population. METHODS: We genotyped three NOS3 SNPs in 426 subjects not treated for arterial hypertension (mean age, 49.1 years; 55.9% women). Arterial properties were measured using applanation tonometry. In multivariate-adjusted analyses, we assessed the gene effects of rs3918226 (-665 C>T), rs1799983 (glu298asp G>T) and rs2070744 (786 T>C) on augmentation index (AIx), central augmentation pressure (AP) and aortic pulse wave velocity (PWV). RESULTS: Carriers of rs3918226 mutated T allele had marginally higher AIx (145.3 ± 2.5 vs. 140.2 ± 1.1%; P = 0.064) and significantly higher AP (12.7 ± 0.7 vs. 11.1 ± 0.3 mm Hg; P = 0.033). These associations were independent of potential confounding factors. Aortic PWV was not different in the two rs39182226 genotypes groups (P = 0.35). In single gene analyses, we did not observe any association between measured phenotypes and rs1799983 or rs2070744 (P ≥ 0.11). In haplotype analysis, we observed trend for higher PWV in haplotypes containing rs3918226 mutated T allele compared with other allelic combination (P ≤ 0.079). CONCLUSION: Mutated T allele of rs3918226 polymorphism in NOS3 gene was associated with parameters reflecting central arterial stiffness and wave reflection. We hypothesize that genetic modulation of intermediate arterial phenotypes might lead to higher blood pressure.
Keywords: mladý dospělý; krevní tlak; Československo; Adult; Young Adult; Haplotypes; lidé středního věku; Genetic Association Studies; Nitric Oxide Synthase Type III; Polymorphism, Genetic; Vascular Stiffness; genetické asociační studie; Czechoslovakia; synthasa oxidu dusnatého, typ III; ženské pohlaví; lidé; haplotypy; mužské pohlaví; senioři; dospělí; Aged; Humans; Female; Middle Aged; tuhost cévní stěny; Blood Pressure; Male; polymorfismus genetický